2016
DOI: 10.1017/s0014479716000120
|View full text |Cite
|
Sign up to set email alerts
|

IMPACT OF THE ADAPTED YAM MINISETT TECHNIQUE ON WARE YAM (DIOSCOREA ROTUNDATA) PRODUCTION UNDER FARMER-MANAGED CONDITIONS IN NIGERIA

Abstract: White yam (Dioscorea rotundata) is a major root crop grown throughout West Africa and a major limitation on its production is the availability of good quality (i.e. free of pests and diseases) planting material; notably seed yams. AYMT is a process by which farmers can produce good quality seed yams using setts treated with a pesticide dip. While previously published studies have focussed on the agronomy of the sett-to-seed yam process there has been no work done on the seed-to-ware yam stage which is critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…The positive impact on tuber weight of treating yam setts before planting is clear from the research presented here and indeed has been noted in previous publications (Morse and McNamara, 2015;2016;Morse et al, 2009). The results also confirm a point made before regarding the effect of pesticide treatment on tuber weight rather than tuber number (Morse and McNamara, 2015).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The positive impact on tuber weight of treating yam setts before planting is clear from the research presented here and indeed has been noted in previous publications (Morse and McNamara, 2015;2016;Morse et al, 2009). The results also confirm a point made before regarding the effect of pesticide treatment on tuber weight rather than tuber number (Morse and McNamara, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Akpaji appears to have lower average tuber weight, weight of tubers/sett planted and number tubers/sett planted relative to the other two varieties. These findings regarding the impact of pesticide treatment and variety were expected and indeed were highlighted in the results of previous work utilising AYMT demonstration plot data from 2013 and 2014 (Morse and McNamara, 2015; 2016).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…An example of agronomic studies for the AYMT can be found in Morse andMcNamara (2016, 2018b). There have also been studies on the agronomic impact of using seed yams produced from AYMT on ware yam production (Morse and McNamara, 2017). However, while the agronomy of YMT and AYMT has been well-explored, there is still a relative paucity of cost-benefit analyses (CBA) of both YMT and AYMT, especially under farmermanaged conditions rather than researcher-controlled experimental plots.…”
Section: Introductionmentioning
confidence: 99%
“…The assumption here is that seed yams produced via any of the techniques is of a better quality than planting material the farmer would otherwise have access to. The agronomic benefits of using quality seed yams produced from AYMT for ware yam production have been explored by Morse and McNamara (2017) but not the economic impacts. Third, almost all of the studies to date, be they based on experiments, surveys or monitoring farmer-managed plots, have not compared the economic performance of untreated and treated setts.…”
Section: Introductionmentioning
confidence: 99%